INFLUENCE OF GEOMETRY AND COOLING RATE ON PROPERTIES OF SINTER-HARDENED STEELS - Ilaria Forno; Marco Actis Grande (Acta Metallurgica Slovaca, 2013)
The aim of this paper is to deepen the understanding of the influence of the cooling step on the final properties of sinter-hardened components, mainly focusing on part geometry (through the definition of an A/M ratio) and cooling rate. A commercial Distaloy DH powder has been uniaxially pressed in different shapes, identified in terms of area/mass index, at three different compacting pressures (500, 600 and 800 MPa). During the sinter-hardening process, conducted in a belt-furnace, temperature profiles and atmosphere have been sampled and analysed. Particular attention has been paid to the cooling step, carried out at different furnace settings (10 to 80% of the maximum cooling capability in terms of fan speed). Sintered samples have been analysed in terms of carbon and oxygen content, hardness and microstructure. The considered properties have then been compared with dilatometer data, derived from literature. Matching these properties, a correlation between furnace setting, shape and microstructure has been drawn.